A Walk in the Woods: The Role of Focus Groups in Finding Meaning - Dijkhuizen, Laura (Journal of European Baptist Studies, 2021)
This article describes the use of methods and the search for a methodology in the research of gender roles within the Dutch Evangelical Movement (DEM). This hermeneutical research is situated in the field of practical theology. The metaphor ‘A walk in the woods’ illustrates in a heuristic way the advantages of focus groups in understanding how meaning is constructed among female leaders within the DEM. Using a narrative approach, the interaction within a specifically convened focus group is combined with the ‘problem tree’ method, in which data already identified is discussed, and possible reasons behind it explored. I argue that working with diverse focus groups provides insights into the theological and social cultural dynamics at play, and reveals within the given frame deeper underlying motivations and actions that bring greater clarity to the actual current (or lived) situation of women within leadership.